2019
DOI: 10.1038/s41598-019-46344-z
|View full text |Cite
|
Sign up to set email alerts
|

Ampicillin-treated Lactococcus lactis MG1363 populations contain persisters as well as viable but non-culturable cells

Abstract: Lactococcus lactis is used as cell-factory and strain selections are regularly performed to improve production processes. When selection regimes only allow desired phenotypes to survive, for instance by using antibiotics to select for cells that do not grow in a specific condition, the presence of more resistant subpopulations with a wildtype genotype severely slows down the procedure. While the food grade organism L. lactis is not often exposed to antibiotics we characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…When prolonged translation inhibition is applied, cell death is inevitable and can be responsible to the decline in product formation to some extent. Antibiotic exposure to Lactococcus lactis has also been reported to induce heterogenous population response regarding dormancy states and the corresponding death rates and metabolic activity ( van Tatenhove-Pel et al, 2019 ). To characterize the effects of erythromycin in our experiments, a combination of CFU counting and live-dead staining measurements was employed to determine how cellular viability and integrity relate to the observed decline in acidification.…”
Section: Resultsmentioning
confidence: 99%
“…When prolonged translation inhibition is applied, cell death is inevitable and can be responsible to the decline in product formation to some extent. Antibiotic exposure to Lactococcus lactis has also been reported to induce heterogenous population response regarding dormancy states and the corresponding death rates and metabolic activity ( van Tatenhove-Pel et al, 2019 ). To characterize the effects of erythromycin in our experiments, a combination of CFU counting and live-dead staining measurements was employed to determine how cellular viability and integrity relate to the observed decline in acidification.…”
Section: Resultsmentioning
confidence: 99%
“…All the strains that were used are listed in Table 1 . L. lactis NZ9000 strains PTSman_GFP, PTScel_GFP, and GlcU_GFP were obtained by a single-crossover integration of vector pSEUDO:: Pusp45-gfp [ 22 ] into the pseudo 10 locus on the chromosome of L. lactis NZ9000∆ ptcC ∆ GlcU , NZ9000∆ ptnABCD ∆ GlcU , and NZ9000∆ ptnABCD ∆ ptcC [ 23 ], respectively. Integration was performed as previously described [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“… [ 28 ] MG1363_GFP L. lactis MG1363 carrying pSEUDO:: P usp45 -gfp . [ 22 ] NZ9000_PTSman_GFP Ery r , NZ9000 ∆ptcC∆GlcU carrying pSEUDO:: P usp45 -gfp . This work NZ9000_PTScel_GFP Ery r , NZ9000 ∆ptnABCD∆GlcU carrying pSEUDO:: P usp45 -gfp .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the contribution of VBNC cells to bioconversion of raw materials has been demonstrated, where for example, it was shown that VBNC Lactobacillus hilgardii can contribute to malolactic fermentation occurring during apple cider production (Quirós et al 2009). Recently, it was described that exposure of L. lactis MG1363 to ampicillin leads to the emergence of both VBNC and persister subpopulations (van Tatenhove-Pel et al 2019). Ampicillininduced persister cells represented only a minor subpopulation (0.3%) when exponentially growing cultures were used, but increased substantially (7.6%) when cells were obtained from the stationary phase of growth (van Tatenhove-Pel et al 2019).…”
Section: The Importance Of Microbial Dormancy In Cheese Productionmentioning
confidence: 99%